The Muslim wives' share in the matrimonial wealth: Between theory and practice - Shaffei, Yomna Amr (AUC Knowledge Fountain, 2018)
This thesis aims at responding to the problem of not monetizing women’s labor in the household through the financial Islamic right of al-Kadd wa al-Se’aya which acknowledges that women are economic partners in the matrimonial wealth in exchange to their labor. The right of al-Kadd wa al-Se’aya has its roots in the Qur’anic in verse 32 in Surat al-Nisaa’ which in one of its interpretations links labor to financial compensation, in the same manner as did Ibn Khaldun, Karl Marx, John Locke and Adam Smith. Furthermore, the thesis attempts to illustrate that the right of al-Kadd wa al-Se’aya was debated among some pre modern Muslim scholars. This financial right was granted to some Muslim women in pre modern Moroccan shari’a courts and granted to some Muslim women in modern times legal systems of Morocco, Indonesia and Malaysia. Lastly, the thesis attempts to assess the applicability of applying the right of al-Kadd wa al-Se’aya in the Egyptian personal status law with illustration of the challenges the calling for its application might face in Egypt. The thesis concludes with recommendations for effectual process to apply the law in Egyptian personal status law.